Diffusing obesity myths. Issue 3 (7th May 2014) - Ramos Salas, X.; Forhan, M.; Sharma, A. M.
Summary Misinformation or myths about obesity can lead to weight bias and obesity stigma. Counteracting myths with facts and evidence has been shown to be effective educational tools to increase an individuals' knowledge about a certain condition and to reduce stigma.The purpose of this study was to identify common obesity myths within the healthcare and public domains and to develop evidence‐based counterarguments to diffuse them. An online search of grey literature, media and public health information sources was conducted to identify common obesity myths. A list of 10 obesity myths was developed and reviewed by obesity experts and key opinion leaders. Counterarguments were developed using current research evidence and validated by obesity experts. A survey of obesity experts and health professionals was conducted to determine the usability and potential effectiveness of the myth–fact messages to reduce weight bias. A total of 754 individuals responded to the request to complete the survey. Of those who responded, 464 (61.5%) completed the survey. All 10 obesity myths were identified to be deeply pervasive within Canadian healthcare and public domains. Although the myth–fact messages were endorsed, respondents also indicated that they would likely not be sufficient to reduce weight bias. Diffusing deeply pervasive obesity myths will require multilevel approaches.